Design and Develop of Open Architecture CNC Movement Control System for Analysing Precision Motion of EDM Machine - Anugraha, Rino Andias; Ibrahim, Mohd Rasidi (International Journal of Integrated Engineering, 2020)
Since the third Industry Revolution (IR3.0), automation become a key technology in industry especially CNC machine. An EDM machine is CNC based that able to reduce the process time, increase the productivity of manufacturing process, and duel with complex task. Therefore, it was one of the best choice to become the education element in manufacturing field. However, high in cost and complexity in structure were the weaknesses and limitations of EDM machine. An open architecture CNC movement control system was studied in order to create a high flexibility, affordable, and simple movement control system for EDM machine. LabVIEW was chosen as the main controller software and NI MyRIO as the main processor in this movement control system. The hardware was built by using open architecture components which reusable and low in cost. This system was able to control the movement of X, Y, and Z axis of the EDM machine in term of distance travel. The time counter in LabVIEW program was used as the feedback system due to absent of encoder as the position feedback element. The relationship between traveled time and distance traveled was determined for the adjustment and programs for single direction, dual direction, specific distance movement, multi axis movement and stop when sensor triggered were developed. The desired value was compared with the actual distance travel in order to calculate the percentage of error of the control system. The percentage of error for X, Y, Z and the gap created was 0.37%, 0.38%, 0.49% and 2.9% respectively. This experimental study will fulfill three objectives. First is to design an open architecture CNC movement control system in X, Y, and Z axis for EDM application. Second is to integrate and analyze the CNC movement control system with the machine hardware. Lastly is to analyze the performance of the developed movement control system with respect to the CNC movement system.